GRAMMATICAL AND LEXICAL ANALYSIS OF THE LYRICS OF THE SONG TAKUT BY BRIGITA MELIALA - Matrawi, Matrawi; Nanda , Fitriya; Keith, Evand Francis (ASMARALOKA: Jurnal Bidang Pendidikan, Linguistik, dan Sastra Indonesia, 2023)
The purpose of this study is to describe how thw forms of grammatical cohesion and lexical cohesion in the lyrics of the song Fear by Brigita Meliala. This analysis uses a qualitative approach, because this study includes detailed and clear explanations of sentences. The data source used was the lyrics of the song Fear by Brigita Meliala which were then analyzed by the researcher. Based on the results of this study, the researcher found some data on aspects of grammatical cohesion and aspects of lexical colletion in song lyrics by Brigita Meliala. In terms of grammatical collections found in the lyrics of the song Fear by Brigita Meliala, they are repetition, affaxation, reference, and chaining. Meanwhile, the aspect of lexical collection found in the lyrics of the song Fear Brigita Meliala is epizeukis repetition cohesion. The grammatical cohesion of reference foud in the lyrics of the song Fear is the word tuebulent, the repetition cohesion is the word twists and dreams, and the cohesion contained in the lyrics of the song Fear is the repetition of epizeukis, namely the words and, I'm afraid.